1973
DOI: 10.1002/pol.1973.170111205
|View full text |Cite
|
Sign up to set email alerts
|

The influence of fine structure on the pyrolysis of cellulose. II. Pyrolysis in air

Abstract: synopsisThe pyrolysis of purified celluloses in air at 251OC was studied. The pyrolysis was found to obey first-order kinetics, and the.rate constants correlated with the crystallinities, orientations and accessibilities of the samples. The results are interpreted in terms of an oxygen-catalyzed decomposition, with the accessibility of oxygen to the cellulose determining the rate of pyrolysis. The production of levoglucosan under conditions approaching combustion was shown to be a function of the crystallinity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0

Year Published

1978
1978
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 6 publications
1
15
0
Order By: Relevance
“…The percentage residue (i.e., the weight remaining after thermal decomposition), and the percentage char (i.e. the weight remaining at 500 ~ were calculated from the TG curves and based on the dry weight of cellulose [4].…”
Section: Thermogravimetrymentioning
confidence: 99%
See 1 more Smart Citation
“…The percentage residue (i.e., the weight remaining after thermal decomposition), and the percentage char (i.e. the weight remaining at 500 ~ were calculated from the TG curves and based on the dry weight of cellulose [4].…”
Section: Thermogravimetrymentioning
confidence: 99%
“…Golova et al [3] reported that the packing density of cellulose altered the amount of levoglucosan formed during vacuum pyrolysis. Basch and Lewin [4] showed that there was a correlation between the crystallinity degree of polymerization and the pyrolysis of cellulose. For a complete understanding of this fact, more analysis needs to be carried out on different cellulose crystal forms.…”
mentioning
confidence: 98%
“…Cellulose with lower crystallinity forms more char and less volatile products including levoglucosan [6][7][8]. Golova et al [7] studied the levoglucosan formation from various kinds of cellulose samples compared with glucose and they reported that levoglucosan yield increases with the increasing crystallinity of cellulose.…”
Section: Introductionmentioning
confidence: 99%
“…However, grafting reactions were carried out in heterogeneous3–6 and homogeneous reaction conditions and all the reported homogeneous reactions were investigated in solvent systems like dimethyl sulfoxide and paraformaldehyde (DMSO/PF) 7, 8, 11, 12. It was reported that crystallinity, crystal size, and degree of polymerization of cellulose greatly affect the pyrrolysis kinetics of high α‐cellulose,9, 10, 13 attributed to the synthetic polymer chains hindering the crystallization of cellulose chain. The thermal behavior of homogeneously grafted high α‐cellulose products in the DMSO/PF solvent system were studied, although the thermal degradation behavior of homogeneously grafted high α‐cellulose products in the DMAc/LiCl solvent system has not been reported so far.…”
Section: Introductionmentioning
confidence: 99%